-6y-3y=26

Simple and best practice solution for -6y-3y=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y-3y=26 equation:


Simplifying
-6y + -3y = 26

Combine like terms: -6y + -3y = -9y
-9y = 26

Solving
-9y = 26

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-9'.
y = -2.888888889

Simplifying
y = -2.888888889

See similar equations:

| 3x+36=9x-6 | | 2(x-6)+7x=15 | | y=1.50x+18 | | 3t-t=9-t | | 33=4x-3 | | 16-3p=2/3p+5 | | -x^2+9-8=0 | | 3(i-2)=2i+1 | | -20-4n+7n-14=-16 | | y-4=1x-2 | | F(X)=3X^2+8 | | -3v=-26 | | 5x+5=20x+65 | | 3n-12=-28+5n | | x+21=54 | | 4x-4.9x^2=0 | | 3w=40-2w | | 8s-17=-24+s | | 7b-2/5=6b-7/5 | | 7y=22.4 | | 9x+8+4x+18=180 | | 100=x-19 | | 3x+24=9x-6 | | 6x+24=6x-24 | | -8x+3(2x-4)-5x+10= | | x+(x+5)+4(x+5)=103 | | 2-1/2n=3n+16 | | 2x+1600=7x | | 4x+5-3x-2= | | x-(6x+5)=45 | | u-8.9=5.57 | | h-4=-10 |

Equations solver categories